The EQ leader instilling passion, creating shared goals, and building meaningful organizations through emotional intelligence - Stein, Steven (John Wiley & Sons, Inc., 2017)
A roadmap to success for tomorrow's leaders, this step-by-step guide provides an evidence-based model for exceptional leadership, and a four-pillar roadmap for real-world practice. --
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Leadership; Emotional intelligence; Emotional Intelligence; Intelligence émotionnelle; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior